2009
DOI: 10.1155/2009/924301
|View full text |Cite
|
Sign up to set email alerts
|

ETV6-RUNX1Rearrangement in Tunisian Pediatric B-Lineage Acute Lymphoblastic Leukemia

Abstract: In this study, Forty-one out of fifty-seven Tunisian children with B-lineage acute lymphoblastic leukemia (B-ALL), and without cytogenetically detectable recurrent abnormalities at the time of the diagnosis, were evaluated by fluorescence in situ hybridization (FISH) for the t(12;21). This translocation leads ETV6-RUNX1 (previously TEL-AML1) fusion gene. 16 patients (28%) had ETV6-RUNX1 rearrangement. In addition to this rearrangement, two cases showed a loss of the normal ETV6 allele, and three others showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…FISH analysis FISH analysis was performed on direct BM cells, as previously described [9] using the LSI AML1-ETO dual-color, dual-fusion translocation probe (Vysis, Downers Grove, IL). The ETO probe was directly labeled with SpectrumGreen, and the AML1 probe was directly labeled with SpectrumOrange.…”
Section: Cytogenetic Analysismentioning
confidence: 99%
“…FISH analysis FISH analysis was performed on direct BM cells, as previously described [9] using the LSI AML1-ETO dual-color, dual-fusion translocation probe (Vysis, Downers Grove, IL). The ETO probe was directly labeled with SpectrumGreen, and the AML1 probe was directly labeled with SpectrumOrange.…”
Section: Cytogenetic Analysismentioning
confidence: 99%
“…In the present study, under-representation of the cryptic TEL/AML1 rearrangement overall ( 8.4% ) and in children (13.6%) is low contrary to the expected high prevalence of 25% in western countries. 4 Hospital-based reports, 5 6 7 9 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 international projects, 1 10 24 multicenter studies, 11 24 and review articles 8 15 indicated existence of geographical differences in distribution of TEL/AML1 worldwide, including India ( Table S1 and S2 ). Global studies indicated the incidence of TEL/AML1 positive B ALL was high ranging from 17% in Spain, 6 18.9% in Brazil, 17 28% in Tunisia, 7 31% in United States, 5 37.5% in Egypt, 14 to 40% in Israel.…”
Section: Discussionmentioning
confidence: 99%
“…Review of online hospital-based reports, international projects, multicenter studies, and review articles 3 4 5 demonstrated a wide variation in global incidence, with incidence in west being ∼25% 4 and lesser in India ( Table S1 and S2 -supplementary material). 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 However, the initial observation of very less number of prognostically favorable TEL/AML1 rearranged B-ALL patients from our tertiary care cancer center in south India prompted focus on evaluating the prevalence of this abnormality. The aim and objectives of the study were to see the prevalence of TEL/AML1 gene fusion in newly diagnosed B-ALL patients, compare with the global distribution of the fusion gene, and evaluate the clinical, pathological, molecular, and cytogenetic features where available in TEL/AML1 positive patients.…”
Section: Introductionmentioning
confidence: 99%
“…A dual-color FISH assay using RUNX1T1 and RUNX1 specific probes (Vysis, Downers Grove, IL) was performed on BM cells, as previously described [11]. The RUNX1T1 probe was directly labeled with Spectrum Orange, and the RUNX1 probe was directly labeled with Spectrum Green.…”
Section: Fish Analysismentioning
confidence: 99%